PERUBAHAN STATUS DESA MENJADI KELURAHAN DI KABUPATEN BANDUNG - Kurniasih, Dewi (Magister Ilmu Pemerintahan, Program Pascasarjana Universitas Islam, 2011)
Changes in the status of the village became a district policy or the government's efforts in order to form a new municipality with the aim of achieving effectiveness and efficiency of service to the community. This was done in order to respond to and accommodate growth and complexity of the interests of public service, especially at village level, including Local Government within the Bandung regency. Based on a discussion of some villages have been feasible to turn into district such as Pamekaran Village, Sadu Village and Soreang Village. While other villages not yet eligible to become a district because there is some requirements that have not met them a less extensive area.